Interpretasi Karakteristik Tangga Nada dan Pola Ritmis Ritual Rambu Solo’ dalam Karya Musik “Sadness and Happiness” - Stefan Arnold William Wowiling; Kardi Laksono; Maria Octavia Rosiana Dewi (Journal of Music Science, Technology, and Industry, 2025)
Purpose: This study aims to interpret the characteristics of scales and rhythmic patterns found in three rituals of the Rambu Solo’ ceremony, namely Ma’lambuk, Ma’marakka, and Ma’badong, into the musical composition “Sadness and Happiness.” The problem addressed is how each ritual forms its musical identity through tone structures and rhythms. Method: The method used is qualitative research with an interpretative approach. Data collection was conducted through observation of documentary videos, literature review, and audio analysis of musical elements from each ritual. The data were then verified and analyzed to identify rhythmic patterns, tone structure forms, and tempos, which were subsequently transformed into a combo mix format with a progressive rock genre. Result and Discussion: The results show that the Ma’lambuk ritual is dominated by complex polyrhythmic patterns utilizing phasing and tension and release techniques, performed improvisationally by several participants. Implication: The Ma’marakka ritual features a minor scale with an added raised third (III#) tone, accompanied by vocal and suling lembang improvisations that evoke a sorrowful lament. The Ma’badong ritual presents song lyrics in a simple minor scale with emphasis on the first (i) and second (ii) scale degrees.